(untitled) (City: History, Culture, Society, 2018)
In Soviet historical science during 1960s-1980s a traditional stereotype of perception of the cruiser “Almaz” as “Southern Aurora” was formed, which had to symbolize similar tendencies of the revolutionary progress in 1917- 1918 in Baltic and the Black Sea Fleets. The role of the steamship crew in events of the Russian and the Ukrainian revolutions in a limited period of time is analyzed in the article. In January 1918, the Bolshevist armed insurrection took place in Odesa, active participation in the preparation of which was played by the part of sailors and officers of the cruiser “Almaz”. During the existence of the Odesa Soviet republic, new authorities used the practice of the “red” terror, the symbol of which was “Almaz”. As the result of the detention and physical liquidation of people of various categories on the cruiser and at moorings of other warships, thus spreading a variety of rumours, authorities of local self-government attempted to take control of the situation in order to make facts of self-trial impossible. But judicial and investigational institutions were able to investigate the circumstances of the detention of prisoners and their subsequent fate fully only after the restoration of the Ukrainian National Republic governance in Odesa. Their conclusions dispel the heroic image of the cruiser created by Soviet historiography.